Binary NiCo nanoalloys and single-atoms implanted nitrogen-doped carbon nanotubes as highly efficient, robust electrocatalyst for overall water splitting - Balasubramanian, Paramasivam; Khan, Hasmat; Baek, Ji-Hu; Kwon, Se-Hun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •NiCo nanoparticles and single-atoms confined by nitrogen doped carbon nanotubes are synthesized.•NiCo-N-CNTs-900 requires lower overpotential at 10 mA cm−2 in OER and HER than the Ni-N-CNTs-900 and Co-N-CNTs-900.•Highly dispersed NiCo nanoalloys and Ni/Co single-atoms structure boost OER and HER.•A water electrolyzer using NiCo-N-CNTs-900 exhibits low cell voltage than the Pt/C//RuO2 couple. Finding robust, high-efficiency, noble-metal-free electrocatalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) particularly at a low overpotential is a crucial endeavor for water electrolyzer-based green H2 harvesting, but challenges remain. Fortunately, atomically dispersed metal catalysts hold great potential for OER and HER owing to the exclusive electronic structure and maximized atom utilization, however, the insufficient population of reactive sites and unfortunate electrical conductivity seriously limit their performance. Herein, we rationally designed and synthesized a single-atom catalyst consisting of atomic Co and Ni with NiCo alloys encapsulated nitrogen-doped carbon nanotubes (N-CNTs). The NiCo-N-CNTs catalyst annealed at 900 °C (NiCo-N-CNTs-900) displays ultralow overpotential of 210 mV and 54 mV at 10 mA/cm2 for OER and HER, respectively, which are attributed to the robust synergistic effects of Ni/Co single atoms and NiCo nanoalloys. Furthermore, NiCo-N-CNTs-900 electrode exhibits higher mass activity of 2188 A/gNiCo and 468.75 A/gNiCo and turnover frequency of 0.679 O2 s−1 and 0.285 H2 s−1 for OER and HER, respectively, which is much better than those of commercial RuO2 and Pt/C catalysts. We further employed the NiCo-N-CNTs-900 as both anode and cathode catalyst for constructing a two-electrode electrolyzer, generating a current density of 10 mA/cm2 at a low cell voltage of 1.483 V, surpassing the benchmark Pt/C//RuO2 pair. This work not only provides a robust and effective non-precious metal catalyst but also a facile, efficient method to fabricate atomically dispersed metal atoms integrated with alloys for clean hydrogen production and beyond.